2006
DOI: 10.1111/j.1440-172x.2006.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between exercise, Body Mass Index and menopausal symptoms in midlife Australian women

Abstract: The main objective of the study was to examine the relationship between physical activity and Body Mass Index (BMI) on menopausal symptoms in Australian midlife women. This study is a secondary data analysis of the Queensland Midlife Women Health Study (2001), which included a randomized, population-based postal survey with a questionnaire. Selected women completed a questionnaire, which included measurement of sociodemographic factors (age, employment and education attainment), general health, use of hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 28 publications
6
70
3
3
Order By: Relevance
“…The effects of exercise in reducing psychological symptoms have been widely reported. A study including Australian midlife women, noted, that exercise was beneficial for somatic and psychological symptoms including depression and anxiety, but not for vasomotor symptoms or sexual function [56].…”
Section: Benefits To Psychological Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of exercise in reducing psychological symptoms have been widely reported. A study including Australian midlife women, noted, that exercise was beneficial for somatic and psychological symptoms including depression and anxiety, but not for vasomotor symptoms or sexual function [56].…”
Section: Benefits To Psychological Symptomsmentioning
confidence: 99%
“…Providing mental distraction and social interaction [26,56] are some of the explanations provided for the psychological benefits associated with exercise participation.…”
Section: Benefits To Psychological Symptomsmentioning
confidence: 99%
“…42 In these three studies, two were conducted by the same author (Llaneza et al 9 , making it difficult to generalize the results. 35,36 Alonso et al 39 used the Kupperman Index, according to the data found in the literature about its widespread use, even with criticism for not addressing urogenital, social and other symptoms related to sexuality. 9,43-45 Mirzaiinjmabadi et al 39 used the Greene Scale, a list of 21 items including psychological, vasomotor and somatic symptoms, which was not exactly designed as an instrument of quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…35,36 Alonso et al 39 used the Kupperman Index, according to the data found in the literature about its widespread use, even with criticism for not addressing urogenital, social and other symptoms related to sexuality. 9,43-45 Mirzaiinjmabadi et al 39 used the Greene Scale, a list of 21 items including psychological, vasomotor and somatic symptoms, which was not exactly designed as an instrument of quality of life. 21,39 The other specific questionnaires were: Menopause Rating Scale (MRS), Women's Health Questionnaire (WHQ) and Menopause-Specific Quality of Life Questionnaire (MEN-QOL), which have already been validated and are the main scales currently used in studies on women in transition to menopause and post-menopause.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation